Association genetics studies on frost tolerance in wheat (Triticum aestivum L.) reveal new highly conserved amino acid substitutions in CBF-A3, CBF-A15, VRN3 and PPD1 genes - Babben, Steve (BMC Genomics, 2018)
BACKGROUND: Understanding the genetic basis of frost tolerance (FT) in wheat (Triticum aestivum L.) is essential for preventing yield losses caused by frost due to cellular damage, dehydration and reduced metabolism. FT is a complex trait regulated by a number of genes and several gene families. Availability of the wheat genomic sequence opens new opportunities for exploring candidate genes diversity for FT. Therefore, the objectives of this study were to identity SNPs and insertion-deletion (indels) in genes known to be involved in frost tolerance and to perform association genetics analysis of respective SNPs and indels on FT. RESULTS: Here we report on the sequence analysis of 19 candidate genes for FT in wheat assembled using the Chinese Spring IWGSC RefSeq v1.0. Out of these, the tandem duplicated C-repeat binding factors (CBF), i.e. CBF-A3, CBF-A5, CBF-A10, CBF-A13, CBF-A14, CBF-A15, CBF-A18, the vernalisation response gene VRN-A1, VRN-B3, the photoperiod response genes PPD-B1 and PPD-D1 revealed association to FT in 235 wheat cultivars. Within six genes (CBF-A3, CBF-A15, VRN-A1, VRN-B3, PPD-B1 and PPD-D1) amino acid (AA) substitutions in important protein domains were identified. The amino acid substitution effect in VRN-A1 on FT was confirmed and new AA substitutions in CBF-A3, CBF-A15, VRN-B3, PPD-B1 and PPD-D1 located at highly conserved sites were detected. Since these results rely on phenotypic data obtained at five locations in 2 years, detection of significant associations of FT to AA changes in CBF-A3, CBF-A15, VRN-A1, VRN-B3, PPD-B1 and PPD-D1 may be exploited in marker assisted breeding for frost tolerance in winter wheat. CONCLUSIONS: A set of 65 primer pairs for the genes mentioned above from a previous study was BLASTed against the IWGSC RefSeq resulting in the identification of 39 primer combinations covering the full length of 19 genes. This work demonstrates the usefulness of the IWGSC RefSeq in specific primer development for highly conserved gene families in hexaploid wheat and, that a candidate gene association genetics approach based on the sequence data is an efficient tool to identify new alleles of genes important for the response to abiotic stress in wheat. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-018-4795-6) contains supplementary material, which is available to authorized users.